The Effect of Prenatal Yoga on The Intensity of Lower Back Pain Among Third-Trimester Pregnant Women: A True-Experimental Study at Namlea Community Health Center - Mentari; Endyka Erye Frety; Euvanggelia Dwilda; Bambang Purwanto (STIKes Budi Luhur Cimahi, 2025)
Background: Low back pain is common among pregnant women, particularly in the third trimester, and is mainly associated with physiological changes, including hormonal fluctuations affecting connective and supportive soft tissues, leading to reduced muscle flexibility and elasticity. Pain management during pregnancy involves pharmacological and non-pharmacological approaches, with this study focusing on prenatal yoga as a non-pharmacological intervention. Objective: To examine the effect of prenatal yoga on reducing the intensity of low back pain in women during the third trimester of pregnancy. Methods: This study employed a true experimental pretest–posttest control group design with 32 samples equally assigned to an intervention group (n = 16) and a control group (n = 16). The intervention was conducted four times over two weeks, with each session lasting 30–60 minutes. Data were collected using a structured checklist and the Numeric Rating Scale (NRS). Statistical analysis used the Wilcoxon signed-rank test and the Mann–Whitney U test. Results: The prenatal yoga group demonstrated a statistically significant reduction in low back pain intensity following the intervention (p = 0.001), with mean pain scores decreasing from 2.00 to 1.29, indicating a mean difference of 0.71. In contrast, the pregnancy gymnastics group showed a smaller reduction, with mean scores declining from 2.06 to 1.82, yielding a mean difference of 0.24. Between-group analysis confirmed a statistically significant difference in pain intensity (p = 0.001). Conclusion: Prenatal yoga significantly reduces the intensity of low back pain in women during the third trimester of pregnancy.